Two-Stage Dynamic Alliance Bidding for Incremental Distribution and Retail Companies Based on Complex Network Theory - Li , Peiyue; Wang , Zhijie; Jin , Jiahui; Li, Guibing (Frontiers in Energy Research, 2022)
As the high energy deviation settlement (EDS) costs, most incremental distribution and retail companies (IDRCs) are at the financial risk. A bidding model of two-stage dynamic alliance based on complex network theory is proposed to maximize IDRCs’ profit in energy and primary frequency regulation (PFR) markets. In medium- and long- term alliance strategy, the potential alliances of IDRCs are updated by the gravity model. The day-ahead alliance bidding is modeled as the bi-level model. The upper level maximizes alliance profits. And the cooperation cost and alliance condition constraints are included. The lower level simulates market clearing to maximize social welfare. Finally, the effectiveness of the proposed model is verified by complex network theory.